The relationship between students and stress in University Utara Malaysia, Kuala Lumpur - Yasotha, Suppiah @ Thangaraj (2022)
This study was conducted to investigate the association between stress and social-demographic factors, family factors, emotional factors, financial factors, and ways to reduce stress levels among postgraduate students at University Utara Malaysia Kuala Lumpur. Purposive sampling was used to establish the sample size for this investigation. The researchers chose survey respondents from the broader community using a non-probability sampling approach called "purposeful sampling." A researcher must have a thorough understanding of the study's goals to choose and contact potential survey participants. A questionnaire was employed as the major data-gathering tool in this experiment. Between October and November of 2021, data was gathered via a survey. Students at University Utara Malaysia in Kuala Lumpur who are at least 18 years old are eligible to take the exam. Additionally, they must be able to read and comprehend both English and Malay. Those who do not match these criteria will be disqualified. Survey takers were required to complete Sections A through C of a questionnaire. To ensure the most accurate results, the Google Form surveys were sent over WhatsApp, Facebook, and WeChat. This paper has been able to find out how stress among students can be influenced by factors such as family, academic, financial, and social.